1971
DOI: 10.1152/ajplegacy.1971.221.5.1260
|View full text |Cite
|
Sign up to set email alerts
|

Role of the pharyngeal plexus in initiation of swallowing

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 0 publications
0
52
0
2
Order By: Relevance
“…Our observation that the highest stimulation frequencies of the pharynx also produced the greatest facilitation suggests that there may exist, at least for the pharynx, a frequencydependent pattern for afferent feedback. In support of this, animal studies have indicated that the facilitation of reflex swallowing by SLN and glossopharyngeal nerve stimulation is also frequency dependent, with an optimal frequency of 30-50 Hz (Sinclair, 1971;Miller, 1972;Jean & Car, 1979;Weerasuriya, Bieger & Hockman, 1980). Although there was a clear shortening of response latency, repetitive stimulation of the pharynx or oesophagus had no consistent effects on the amplitude of cortically evoked responses.…”
Section: Interaction Between Pathways From Each Hemispherementioning
confidence: 92%
“…Our observation that the highest stimulation frequencies of the pharynx also produced the greatest facilitation suggests that there may exist, at least for the pharynx, a frequencydependent pattern for afferent feedback. In support of this, animal studies have indicated that the facilitation of reflex swallowing by SLN and glossopharyngeal nerve stimulation is also frequency dependent, with an optimal frequency of 30-50 Hz (Sinclair, 1971;Miller, 1972;Jean & Car, 1979;Weerasuriya, Bieger & Hockman, 1980). Although there was a clear shortening of response latency, repetitive stimulation of the pharynx or oesophagus had no consistent effects on the amplitude of cortically evoked responses.…”
Section: Interaction Between Pathways From Each Hemispherementioning
confidence: 92%
“…The reflexive pharyngeal swallow and laryngeal adduction may be activated by stimulation of the internal branch of the superior laryngeal nerve of the vagus (CN X) and the pharyngeal branch of the glossopharyngeal nerve (CN IX) in both animals and humans (Doty 1951; Doty and Bosma 1956; Sinclair 1971; Ludlow et al. 1992; Barkmeier et al.…”
Section: Introductionmentioning
confidence: 99%
“…Among these functions, the swallowing in the pharynx is elicited by the afferent impulses in the glossopharyngeal nerve, and followed by a contracting of the esophagus5,6). However, electric stimulation of the glossopharyngeal nerve inhibits swallowing7, 8). Such a discrepancy in the swallowing response suggests that particular patterns of impulses initiate or inhibit swallowing6,9,10).…”
Section: Introductionmentioning
confidence: 99%